What's Driving Investment in China? - Barnett, Steven (IMF Working Papers; Working Paper, 2006)
Investment has grown rapidly in China in recent years, reaching more than 40 percent of GDP. Despite good progress on bank and enterprise reforms, weaknesses remain that could contribute to inefficient investment decisions. Manufacturing, infrastructure, and real estate have been the drivers of fixed asset investment. Econometric analysis presented in the paper suggests that manufacturing investment is strongly correlated with firms' liquidity, largely retained earnings. Analysis of residential real estate investment shows that it is weakly correlated with real household income growth and real mortgage interest rates. A policy implication of these findings is that reducing liquidity in firms, for example by requiring state-owned enterprises to pay dividends to the government, and using monetary policy to reduce liquidity increase real interest rates, would slow investment in manufacturing and real estate.